Learning Analytics of Critical Reading Activity: Reading Hayavadana during Lockdown (International Conference on Computers in Education, 2020)
Investigating learning behaviors in a humanities course using learning analytics techniques is underrepresented in literature. A Critical Analysis of Literature and Cinema course was selected as a context. The course was offered for more than 10 years by the instructor in a face-to-face classroom mode. However, this time the context was unique as the classroom based interactive activities were rapidly migrated to online sessions due to the COVID-19 pandemic related lockdown. Under such a circumstance, BookRoll, a learning analytics enhanced eBook platform supported the critical reading activity online. Students (n=22 out of the 50 registered) accessed Hayavadana, an Indian play titled Hayavadana uploaded on BookRoll and attempted to identify performative elements and cultural references in the text and highlight them. In this study, we analyze learner’s reading logs gathered in the learning record store linked to BookRoll during that activity. Based on learner’s online reading engagement from their clickstream interactions and time spent for them, four readers' profiles were defined; Effortful, Strategic, Wanderers and Check-out. We illustrate the content navigation and annotation behavior of each of those profiles. This study aims to initiate further discussion related to the application of learning analytics in humanities courses both to enhance the teaching and learning experiences by the use of interactive learning dashboards that was used to probe into the learning behaviors of the students.